The Firm Value of Coal Mining Companies in Indonesia Before and After Government Regulation No. 15 Year 2022 - Mayangsari, Sekar; Koerniady, Arief (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
The influence of PP 15/2022 on the relationship between coal commodity prices cannot be predicted with certainty. Before PP 15/2022 was enacted, coal commodity prices tended to rise and fall according to global and regional market demand and vice versa. The study analyses coal commodity prices and business value before and after PP 15 of 2022, mediated by profitability. This research includes quantitative causal studies. The population of this research is all coal sector companies registered on BEI A12 (Coal) during the research period, namely from 2019-2022; a total of 43 companies and 25 companies were sampled using a purposive sampling technique. This research uses quantitative data, namely data measured on a numerical scale. The type of data used by researchers is secondary data. This research found that coal commodity prices affect firm value before and after PP No. 15/2022. Coal commodity prices impact profitability and substantial discount if the outcomes differ before and after. Strong value is indirectly affected by coal commodity prices via profitability; hence, profitability is a full mediator. Coal to commercial value. That's only true if outcomes match before or after.